Varför äter du inte? : En studie om nyhetsmediers framställning av undernäring inom äldreomsorgen - Sandelin,Artur (2020)
The aim of this study was to explore how newspapers in Sweden present malnutrition within the eldercare by examining the characteristic, causes and solution presented of the issue. The study was based on a qualitative thematic analysis of 39 articles from four different newspapers. The empirics are analyzed with social constructivist theory using Herbert Blumer’s theory about social problems as a product of a collective definition process and John Kitsuse and Malcom Spector theory of claims-making activities. This study uses these theories to understand the way in which malnutrition is constructed and presented as a social problem regarding to its context. The results showed that the articles often focused on the causes of malnutrition within the eldercare, based on three different themes: the quality of the food, the staff’s level of competence and financial cuts of budget or staff. Regarding to which themes chosen the solution was often indirectly implied. Based upon medias great impact in the views of the public, this study wants to further the discussion of possible consequences of this divided and simplistic presentation of malnutrition within elderly care.
Keywords: malnutrition; elderly care; mass media; construction of social problem